HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU DENGAN STATUS GIZI PADA ANAK BALITA - Rissa Nurdiana (Jurnal Medika Hutama, 2021)
Nutritional status is a healthy state of human body, which can be determined by sufficient nutrition to be used by one’s body. One factor contributing to toddlers’ nutritional status is mothers’ knowledge and attitudes. The study was aimed at determining correlations between levels of mother’s knowledge and attitudes and toddlers’ nutritional status. This was a quantitative study with observational analysis using case control design. The population was 80 participants comprising 20 participants of case population and 60 participants of control population, while the samples for this study were 20 of case samples and 60 of control samples. Totality sampling technique was applied, with 20 participants for case samples and 60 participants for control samples. Chi-square test was used for univariate and bivariate analyses in order to determine the correlation between mothers’ attitudes and toddlers’ nutritional status. However; bivariate analysis on the correlation between the levels of knowledge and nutritional status could not be accomplished due to homogenous data. The instrument used in this study was questionnaire, and the result showed that there were no significant correlations between mothers attitudes and nutritional status of toddlers (P value = 0,176). It is expected for next researchers to add more samples to avoid selection bias and to get samples from the previous one year.